Strengthening Capital For Msme Actors In The Mosque Environment Through Microfinancing Of Bank Syariah Indonesia At The Management Of Takmir Masjid Al-Irsyad Kertonegoro Village, Jenggawah District, Jember Regency - Shodiqin, Dimas Herliandis; Huda, Hairul; Syafi'i, Muhammad (Universitas Muhammadiyah Jember, 2023)
Problems in capital in a business field are sometimes the main obstacle for some people who are starting a business, especially the business categorized as MSMEs. There are many factors why MSME actors sometimes have difficulty accessing capital to the banks, such as the absence of guarantees, social gaps and lack of education and information for MSME actors in accessing capital. This can be due to the lack of knowledge and information media so that they are constrained in understanding and utilizing these opportunities to banks. Therefore, Bank Syariah Indonesia Jember branch has financing products for capital for MSMEs, especially among mosque administrators who have businesses. Solusi provides education and information to mosque administrators who have businesses to be able to access capital from BSI. Target Output provides education and information in accessing business capital. The results of this activity concluded that the management of the Al-Irsyad mosque takmir was greatly helped by this activity because it received information and access to business capital applications from BSI Jember